Comparative efficacy of cisternal drainage versus external ventricular drainage in severe aneurysmal subarachnoid hemorrhage - Mahamat Hamid Mahamat; Tuo Li; Jun Liu; Shusheng Zhang; Ye Miao; Zhongzhen Li; Yadan Li; Hua Yan; Guobin Zhang; Xiaoguang Tong (PLoS ONE, 2026)
Background The cerebrovascular emergency known as aneurysmal subarachnoid hemorrhage (aSAH) is potentially fatal. Although external ventricular drainage (EVD) is the gold standard for monitoring intracranial pressure (ICP), cisternal drainage (CD) should be considered as a supplementary strategy due to the limited effectiveness of EVD in removing inflammatory mediators and preventing vascular damage. Objective To compare ICP monitoring accuracy, cerebrospinal fluid (CSF) clearance, and clinical outcomes between EVD and CD in severe aSAH patients. Methods A retrospective study enrolled 47 Hunt-Hess IV–V grade aSAH patients, divided into EVD (n = 23) and EVD + CD (n = 24) groups. Daily ICP values (days 1/3/5/7), CSF biomarkers (cell count, protein, Interleukin-6, Interleukin-8, Tumor Necrosis Factor-α, Endothelin-1, Monocyte Chemoattractant Protein-1, Vascular Cell Adhesion Molecule-1), hospitalization duration, and 6-month Glasgow Outcome Scale (GOS) were analyzed. Results ICP values showed no significant difference between the two groups ( p > 0.05). EVD + CD group exhibited higher CSF cell count (394.68 ± 91.32 vs. 320.40 ± 75.49), protein (16.17 ± 2.27 vs. 13.74 ± 2.94 g/L), and cytokines (IL-6/IL-8, p < 0.05) on day 1, but significantly lower levels by day 7 ( p < 0.05). Vascular injury factors (ET-1/MCP-1/VCAM-1) were reduced in the EVD + CD group by day 7 ( p < 0.05). Hospitalization duration was 22.8% shorter in the EVD + CD group (27 vs. 35 days, p = 0.030); while 6-month GOS showed no difference (2.52 vs. 2.57, p = 0.148). Conclusion Compared with EVD, CD could not only provide accurate ICP readings and trend data but also enhance inflammatory clearance, reduce hospitalization time, and mitigate vascular injury in severe aSAH, warranting further validation in larger cohorts.